Satisfaction Survey for Parents - A study with Special Reference to A Primary School in Vapi, Gujarat - Desai, Devang J.; Patel, Pankajray (Indian Journal of Marketing, 2006)
In the past, the need to market their service has not really been felt by the education sector, as educational institutes, be it schools, colleges or universities, especially in developing countries like ours, have always faced more demand than they could cope with. In some instances, there used to be only few schools in the town and people didn't have much choice about the selection of schools. So in that situation there wasn't any need felt for marketing of primary educational services. But now, due to the attractive potential and advent of private schools in this field, more and more schools are coming up and competitive situation is slowly changing. People have also become more conscious about education and now they have a number of alternatives available to make choice. This field has a high growth potential and due to this reason it is expected that in the near future more and more schools will be established. Because of difference in style of teaching, quality of teaching, facilities provided by schools, parents have become more particular about selecting the school for their child. Even the schools facing heavy demand have been confronted with the question of being able to choose the desired kind of target customers.